Frequency of Use and Standards of Care for the Use of Azathioprine and 6-Mercaptopurine in Treatment of Inflammatory Bowel Disease: A Systematic Review of the Literature and a Survey of Canadian Gastroenterologists - Thomas M Wallace; Sander JO Veldhuyzen van Zanten (Canadian Journal of Gastroenterology)
OBJECTIVE: To identify the frequency of use and appropriate monitoring guidelines for the adverse effects of azathioprine and 6-mercaptopurine (6-MP) in the therapy of patients with inflammatory bowel disease (IBD).